Pemanfaatan Festival Unta Sebagai Upaya Diplomasi Publik Arab Saudi dalam Merekatkan Regionalisme Timur Tengah - Prihandono Wibowo; Muhammad Ahsanul Hakam; Kelvin Dwi Fardani (Faculty of Social Science, Universitas Negeri Padang, 2022)
The use of camels as a regional binder is implemented in the camel race event which has been held since 1999 by local Bedouin tribes and has received attention from the Saudi Arabian royal family, with the holding of this camel event is expected to provide a good political element as public diplomacy for the creation of regional integration in the East. Middle. In this journal the author will use the theory of regionalism and social identity to support the concept of public diplomacy, briefly, regionalism is a tendency in a region based on homogeneity, characteristics, and the provision of cooperation, in line with regionalism social identity theory also has an explanation that individual social identity (in this case the country) affects the dynamics in the regional group. In writing this journal, the writer uses the descriptive analysis method to describe and collect data from various secondary sources. The presence of an adhesive element in the form of a symbol that can be agreed upon collectively able to minimize the presence of words of disagreement is considered capable as the first step to gluing the area. Meanwhile, from the process, the procurement of the largest camel festival in the world that can present representatives of countries in the Middle East Region Saudi Arabia is considered capable of being a promotional event for the adhesive symbol.